Prognosis of poorly cohesive gastric cancer after complete cytoreductive surgery with or without hyperthermic intraperitoneal chemotherapy (CYTO-CHIP study). Issue 10 (9th September 2021) - Bonnot, P E; Lintis, A; Mercier, F; Benzerdjeb, N; Passot, G; Pocard, M; Meunier, B; Bereder, J M; Abboud, K; Marchal, F; Quenet, F; Goere, D; et al.
Abstract: Background: The incidence of gastric poorly cohesive carcinoma (PCC) is increasing. The prognosis for patients with peritoneal metastases remains poor and the role of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is controversial. The aim was to clarify the impact of gastric PCC with peritoneal metastases treated by CRS with or without HIPEC. Methods: All patients with peritoneal metastases from gastric cancer treated with CRS with or without HIPEC, in 19 French centres, between 1989 and 2014, were identified from institutional databases. Clinicopathological characteristics and outcomes were compared between PCC and non-PCC subtypes, and the possible benefit of HIPEC was assessed. Results: In total, 277 patients were included (188 PCC, 89 non-PCC). HIPEC was performed in 180 of 277 patients (65 per cent), including 124 of 188 with PCC (66 per cent). Median overall survival (OS) was 14.7 (95 per cent c.i. 12.7 to 17.3) months in the PCC group versus 21.2 (14.7 to 36.4) months in the non-PCC group ( P < 0.001). In multivariable analyses, PCC (hazard ratio (HR) 1.51, 95 per cent c.i. 1.01 to 2.25; P = 0.044) was associated with poorer OS, as were pN3, Peritoneal Cancer Index (PCI), and resection with a completeness of cytoreduction score of 1, whereas HIPEC was associated with improved OS (HR 0.52; P < 0.001). The benefit of CRS-HIPEC over CRS alone was consistent, irrespective of histology, with a median OS of 16.7 versus 11.3 months (HR 0.60, 0.39 to 0.92; P = 0.018) in the PCC group, and 34.5 versus 14.3 months (HR 0.43, 0.25 to 0.75; P = 0.003) in the non-PCC group. Non-PCC and HIPEC were independently associated with improved recurrence-free survival and fewer peritoneal recurrences. In patients who underwent HIPEC, PCI values of below 7 and less than 13 were predictive of OS in PCC and non-PCC populations respectively. Conclusion: In selected patients, CRS-HIPEC offers acceptable outcomes among those with gastric PCC and long survival for patients without PCC. Abstract : Despite cytroreductive surgery (CRS) with or without HIPEC remains higly controversial in gastric peritoneal carcinomatosis namely concerning signet ring cell and poorly cohesive cell carcinomas, adjuvant HIPEC after complete CRS offers substantial survival benefits and reduces the rate of peritoneal reccurence whatever the histology versus CRS alone. Histology should represent a major criterion in the oncological strategy.